Seroprevalence of Human Immunodeficiency Virus (HIV), Hepatitis B Virus (HBV), Hepatitis C Virus (HCV) and Syphilis among Voluntary Blood Donors in Rural Southwestern Uganda: A Retrospective Study - Apecu, Richard Onyuthi; Mulogo, Edgar Mugema; Bagenda, Fred; Byamungu, Andrew; II, Yap Boum; Bazira, Joel; Byarugaba, Frederic (International journal of tropical disease & health, 2017)
Despite the improvement with blood screening, transfusion transmissible infectious (TTIs) agents such as human immunodeficiency virus (HIV), hepatitis B virus (HBV), hepatitis C virus (HCV) and syphilis are still among some of the challenges in the blood safety for the recipient in Uganda. The aim of this study was to determine the prevalence of the four TTIs among the voluntary blood donors in southwestern Uganda. A retrospective study was conducted using one-year data (January 2014 to December 2014) from a regional blood bank in southwestern Uganda. Routine screening by the blood bank included anti HIV, hepatitis B surface antigen, anti-hepatitis C using the Abbott ARCHITECT i2000 SR analyzer. Both Rapid Plasma Reagin (RPR) test and Treponema Pallidun Haeagglutination (TPHA) tests were used for detection of syphilitic infection. 5.67% of blood donors were positive for any of the screening tests and 0.34% had multiple infections. The overall seroprevalence was 1.03%, 1.87%, 2.22%, and 0.54% for HIV, HBV, HCV and syphilis respectively. The most common dual combinations were HBV-HCV 51.8 %, HIV-HCV 22.7% and HIV-HBV 10.0%. Triple infection with HIV-HBV-HCV was 3.7% and HIV- HBV-Syphilis was 1.3%. There were no quadruple infections detected in this study. There was statistically significant increase of HIV seropositivity among the age group of donors above 47 years (p=0.001). A substantial prevalence of TTIs was found among the blood donors in southwestern Uganda.
Keywords: HIV; HBV; HCV; Syphilis; Prevalence; TTIs; Uganda